The Role of Employee Engagement as a Mediation of The Relationship Between Psychological Empowerment and Human Resource Practices on Job Satisfaction - Haryanto, Bayu; Sri Mulatsih, Listiana; Yuliviona, Reni (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
This research aims to analyze the relationship between psychological empowerment and human resource practice with job satisfaction mediated by employee engagement. The respondents in this study were all educational staff at a private university in Padang City, Indonesia, which numbered as many as 130 employees using census techniques. Data collection method using a questionnaire with measurement of research variables using a survey questionnary based on the Likert-5 scale. The data analysis model in this study was tested using SmartPLS software version 4.0.9.5. Research findings show that psychological empowerment affects employee engagement, psychological empowerment affects job satisfaction, and human resource practice affects job satisfaction. Human resource practices have no influence on employee engagement. Employee engagement have no influence on job satisfaction. Employee engagement does not mediate the relationship between psychological empowerment and job satisfaction. Employee engagement does not mediate the relationship between human resource practice and job satisfaction.